Molecular interaction analysis of the lignans from Piper cubeba in complex with Haemonchus contortus phosphomethyltransferase - Borges, Alexandre [UNESP]; de Oliveira, Ivan Pires; Lescano, Caroline Honaiser; Parreira, Renato Luis Tame; Orenha, Renato Pereira; da Silva de Laurentiz, Rosangela [UNESP] (Elsevier, 2023)
In vitro larvicidal assays carried out previously by our research group with cubebin, dihydrocubebin and hinokinin, lignans extracted from the fruits of Piper cubeba, against Haemonchus contortus larvae showed strong action larvicidal these compounds. Hinokinin was the most active (EC50 = 0.34 µg/mL) with strong action on the cuticle of the larvae as observed by scanning electron microscopy of the L3 stage. Therefore, to understand the mechanism of action of these compounds in silico studies were carried out using the enzyme phosphomethyltransferase of Haemonchus contortus that contain PMT-1 and PMT-2 di-domains responsible for phosphocholine synthesis, which is one of the main lipids in nematodes. This pathway is not found in mammals, so this enzyme is an important biological target for the development of new anthelmintics. Results of molecular docking, molecular dynamic and a density functional theory calculations studies with the three lignans show few interactions with PMT-1. However, hinokinin has important interactions with PMT-2, that can deactivate the enzyme and interrupt the phosphocholine synthesis, which is an essential compound for the development and maintenance of the nematode cuticle and its survive. Therefore, the previous results of the in vitro assay allied with in silico results, now realized; suggest that hinokinin may be a possible selective target for the development of new anthelmintics against Haemonchus contortus since the PMT-2 domain is present in this nematode.
Keywords: Haemonchus contortus; Lignans; Molecular docking; Molecular dynamic; Theoretical calculations